Riparian plant species offer a range of organic resources to stream invertebrate communities through varied leaf breakdown rates. Issue 1 (2nd January 2023) - Hogsden, Kristy; O'Brien, Sophie; Bartlett, Stacey; Warburton, Helen; Devlin, Hayley; Collins, Kathryn; Febria, Catherine; Goeller, Brandon; McIntosh, Angus; Harding, Jon
ABSTRACT: Riparian plants provide an important source of energy for freshwater food webs through inputs of leaf litter. Planting riparian buffers with mixed species could enhance the detrital resource supply for invertebrates through varied leaf breakdown rates. To quantify leaf breakdown rates and invertebrate colonisation, we used leaves from eleven grass, shrub and tree species common along agricultural waterways in New Zealand. Breakdown of leaves immersed in a spring-fed stream differed significantly among species, being fastest for pasture grass ( k  = 0.0458 day −1 ) followed by broadleaf, pittosporum, willow, toetoe, poplar, gorse, Carex, eucalyptus, flax, and slowest for cabbage tree leaves ( k  = 0.0099 day −1 ). Invertebrate community composition did not differ between leaf species, but consumers were extremely abundant on some leaves (e.g. 51–83 Potamopyrgus snails g −1 pasture grass), indicating coarse detrital resources were in high demand for food or habitat. These breakdown rates could inform selection of riparian plant combinations that will enhance food availability for stream communities, especially continuity of supply, thereby contributing to waterway restoration.